IMPLEMENTASI ENTERPRISE GOVERNMENT DI KABUPATEN KUTAI KARTANEGARA - Sudirman Sudirman (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2013)
Efforts to implement the concept of enterprise government a relevant in Kutai Kartanegara Regency because of the setting: high dependence on the mining sector (non-renewable resources) whose role has begun to decline while the District Own Source Revenue/PAD is expected to replace the role of the mining sector still has a low contribution even decreasing trend.However, efforts to implement enterprise government in Kutai Kartanegara Regency will be constrained by the paternalistic culture of bureaucracy. It can be seen from the recruitment and development of civil servants is an important determinant. The study results showed it implies: (1) a low efficiency and effectiveness in spending, and (2) lack of innovation and creativity in exploring new sources of revenue.At the planning level, the government has implemented the principles of enterprise government such as the formulation of vision, mission and goals. But at the level of implementation tend to ignore the principles of efficiency, effectiveness, creativity and innovative. Therefore, this process is called ‘pseudo’ enterprise government. Key words: enterprise government, efficiency, effectiveness, innovation, and creativity